Genotoxicity assessment of atrazine in the Big Blue® Rat2 lacI transgenic cell line - Kim, Y.-J.; Ryu, J.-C. (Kluwer Academic Publishers, 2012)
Atrazine, one of the herbicide, is classified as a possible human carcinogen that may cause breast and ovarian cancers. The mutagenic and genotoxic properties of atrazine have been studied using a variety of assays in the past but the results were contradictory. This fact indicates that a more comprehensive assessment of the potential genotoxicity of atrazine is needed. For this reasons, we investigated the mutant frequency on lacI gene and induction of binucleated micronuclei formation by atrazine in vitro using the Big Blue® Rat2 lacI transgenic fibroblasts, which are transfected by a lambda shuttle vector. These assays carried out at the concentrations of 261. 7, 130. 8 and 65. 4 μg/mL of atrazine, the highest concentration giving 80% survival. These two endpoints were used to compare the induction of point mutations with cytogenetic damages by atrazine under same exposure condition. No significant changes of mutant frequency and binucleated micronuclei frequency induced by atrazine were observed both in the transgenic mutagenesis assay and cytokinesis blocking assay in the absence of metabolic activation system using the Big Blue® Rat2 lacI transgenic fibroblasts. These results suggest that atrazine did not induce mutation and cytogenetic damage in this experimental system. ？ 2012 Korean Society of Environmental Risk Assessment and Health Science and Springer Science+Business Media Dordrecht.
Keywords: atrazine; tissue factor pathway inhibitor; animal cell; article; cell survival; cell viability; controlled study; cytokinesis; cytotoxicity; fibroblast; genotoxicity; micronucleus; mutagenesis; mutagenicity; nonhuman; point mutation; rat; transgene